1961 Meletean - University of Wisconsin-River Falls (University of Wisconsin-River Falls, 1961)
Online, digitized version of the Wisconsin State College, River Falls yearbook for 1961. The 1961 Meletean includes 176 pages of text and photographs. This digital copy was created by Pang Thao in 2011.
Meletean 1961
176 p. divided into 5 parts: Part 1 = Cover and Pages 1-25; Part 2 = Pages 26-55; Part 3 = Pages 56-103; Part 4 = Pages 104-123; Part 5 = Pages 124-176 and Back Cover. Part 1 contains the introduction and photographs; Part 2 contains photographs of the Administration, Faculty and Staff and photographs of Special Events; Part 3 contains photographs and descriptions of Organizations on campus; Part 4 contain photographs and a description of Athletics on campus; and Part 5 contains individual class photographs. Editors: Anne Adams and Carol Truttschel. Assistant Editor: Nancy MacNeil. Editorial Assistants: Francis O'Connell and Keith Olson. Art Editors: Barbara Nelson and Robert Radatz. Sports Editor: Warren Rogers. Photographers: Don Blegen and Wayne Harmann. Advisor: James Harless.
Keywords: College year book; Yearbook; University year book; University of Wisconsin-River Falls--Students--Yearbooks; College yearbook; Year book; Class of 1961 year book; 1961 year book; 1961 yearbook; School yearbooks--Wisconsin--River Falls; Class of 1961 yearbook; University yearbook